International trade and development - Meier, Gerald M. (New York, Harper & Row, 1963)
The book focuses on determining how the structure of comparative advantage changes over time. It also considers the monetary theory of trade and relates the problem of maintaining balance of payments equilibrium to the developmental problem of capital accumulation
Includes bibliography.
osc 30/01/2019
Loans
Keywords: International economic relations; Economic development